Multimodal Handheld Probe for Characterizing Otitis Media — Integrating Raman Spectroscopy and Optical Coherence Tomography - Monroy, Guillermo L.; Fitzgerald, Sean T.; Locke, Andrea; Won, Jungeun; Spillman, Jr., Darold R.; Ho, Alexander; Zaki, Farzana R.; Choi, Honggu; Chaney, Eric J.; Werkhaven, Jay A.; Mason, Kevin M.; Mahadevan-Jansen, Anita; et al. (Frontiers in Photonics, 2022)
(Out of date - new version has tracked changes within) Otitis media (OM) is a common disease of the middle ear, affecting 80% of children before the age of three. The otoscope, a simple illuminated magnifier, is the standard clinical diagnostic tool to observe the middle ear. However, it has limited contrast to detect signs of infection, such as clearly identifying and characterizing middle ear fluid or biofilms. Collecting accurate diagnostic factors is vital for clinicians to deliver a precise diagnosis and effective treatment regimen. To address this need, a combined benchtop Raman spectroscopy (RS) and optical coherence tomography (OCT) system was developed. Together, RS-OCT can non-invasively interrogate the structural and biochemical signatures of the middle ear under normal and infected conditions. In this paper, in vivo RS scans from pediatric clinical human subjects presenting with OM were evaluated in parallel with RS-OCT data of physiologically relevant in vitro ear models. Component-level characterization of a healthy tympanic membrane and malleus bone, as well as OM-related middle ear fluid, identified the optimal position within the ear for RS-OCT data collection. To address the design challenges in developing a system specific to clinical use, a prototype non-contact multimodal handheld probe was built and successfully tested in vitro. Design criteria have been developed to successfully address imaging constraints imposed by physiological characteristics of the ear and optical safety limits. Here, we present the pathway for translation of RS-OCT for non-invasive detection of OM.